Pengembangan Aplikasi Geogebra Berbasis Budaya Batak Untuk Meningkatkan Kemampuan Visual Thinking Matematis Siswa - Dian Fatma Diva; Nur Rahmi Rizqi; Ayu Rahmawati; Sakdiah Aini Rangkuti; Fitry Khairany Pulungan; Melani Prasiska; Nurhabibi Fakhri (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2024)
This study evaluates the impact of developing a culturally grounded GeoGebra application on students' mathematical visual thinking abilities. Against the backdrop of a dearth of educational applications catering to local cultures, the research aims to address this gap. The methodology encompasses pre-test and post-test assessments, learning motivation surveys, classroom observations, and interviews with both students and educators. Data analysis reveals a significant enhancement in students' mathematical visual thinking abilities following the utilization of the application, accompanied by an upsurge in their learning motivation levels. These findings are corroborated by classroom observations and interviews, underscoring the application's role in augmenting student engagement and facilitating a more concrete understanding of mathematical concepts. The implications of this study underscore the significance of integrating culturally grounded educational technology to enhance the efficacy of mathematics education within the students' cultural contexts